Systematic Literature Review: Apakah Media Pembelajaran Mampu Mempengaruhi Hasil Belajar Matematika? - Ice Dwi Novelza; Rhomiy Handican (Griya Journal of Mathematics Education and Application, 2023)
Learning media is one of the means that can increase the effectiveness and efficiency of teaching and learning activities. The purpose of this study was to examine the effect of using instructional media on student learning outcomes in mathematics. Data is collected through related journals for review. The method used in this study is the SLR (Systematic Literature Review) method. Researchers collect accredited national journal articles sourced from the Google Scholar database with the help of the Publish Or Perish application. The articles used in this study were 16 articles from accredited national journals at Sinta 1 to Sinta 4 obtained from Google Scholar and Publish Or Perish. The articles collected are only articles published in the 2018-2022 timeframe. The results of the study indicate that the use of learning media in learning mathematics is very influential in generating interest and motivation in students and has an impact on student learning outcomes.